MAIN TRENDS OF UKRAINE’S FOREIGN TRADE IN GOODS OF LIGHT INDUSTRY - Тернова, Алла; Власенко, Ірина (SWorldJournal, 2025)
The article identifies the main trends in the development of foreign trade in light industry goods of Ukraine under the influence of the manifestation of crisis phenomena caused by military operations on the territory of Ukraine. It is shown that the ligh